Obstacles to implementing strategies in Syrian general industrial companies A case study of Jableh Spinning Company - سليطين, سوما (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of this research is to study the obstacles to implementing strategies in one of the Syrian general industrial companies, which is Jableh Spinning Company. By questionnaire, it is distributed to all members of the research community, which represented by managers at all levels of the company, and they are 43 managers. The most important results of the research were as follows: Jableh Spinning Company suffers from a set of obstacles that prevent the implementation of its strategies, the most important of which related to the following: leadership, organizational culture and organizational structure diagnosis, Staff skills and training, participation and engagement, available resources, performance management, and external events. ..... The most important recommendations are: 1-Jableh Spinning Company must do the following: _ Modifying strategies to suit the change _ holding effective and continuous internal and external training courses that will develop managers and employees and provide them with the necessary capabilities to implement the steps and methods of implementing the strategies properly -Effective employee engagement. 2 _ Concerned authorities must supply the necessary funding for the company to be able to implement its strategies